Goodbye wifes and daughters - Resnick, Susan Kushner (University of Nebraska Press, 2010)
One morning in 1943, close to eighty men descended into the Smith coal mine in Bearcreek, Montana. Only three came out alive. "Goodbye wifes and daughters . . ." wrote two of the miners as they died. The story of that tragic day and its aftermath unfolds in this book through the eyes of those wives and daughters, women who lost their husbands, fathers, and sons, livelihoods, neighbors, and homes, yet managed to fight back and persevere. The author has uncovered the story behind all those losses. She chronicles the missteps and questionable ethics of the mine's managers, who blamed their disregard for safety on the exigencies of World War II. Also recounted are the efforts of an earnest federal mine inspector and the mine union's president (later a notorious murderer), who tried in vain to make the mine safer, as well as the heroism of the men who battled for nine days to rescue the trapped miners; and the effect the disaster had on the entire mining industry. She illuminates a particular historical tragedy with all its human ramifications while also reminding us that such tragedies caused by corporate greed and indifference are with us to this day.